Analisis Manajemen Sumber Daya Manusia terhadap Peningkatan Karir Tenaga Kerja di Era Digital pada sebuah Instansi/Organisasi - Fauziah, Siti Nuraini; Arnu, Anggi Pasca (Jurnal Ilmiah Wahana Pendidikan, 2025)
This research aims to analyze the role of human resource management (HR) in improving the careers of workers in the digital era in an agency/organization, with a focus on adaptation to technological developments and the need for quality human resources. This research method involves a case study at XOXO Coffee Pondok Hijau Bekasi Branch as a representation of an organization in facing the challenges of the digital era. A qualitative research approach was used by collecting data through interviews, observations, and document analysis related to HR management and career development. The research results highlight the importance of effective HR management in designing competency-based recruitment policies, digital skills development, and performance assessments that are adaptive to technological changes. Organizations need to ensure that workforce careers can continue to develop in line with advances in digital technology. The findings of this research provide insight into HR management strategies and implementation that support employee career advancement in the digital era, contributing to the literature on human resource management and career development.